The Effect of Education and Training Program, Facilities and Infrastructure Completeness, Organizational Support on Employee Performance Through Satisfaction as Variable Mediation - Yuniarti Yuniarti (Budapest International Research and Critics University, 2022)
The purpose of this study was to determine the effect of education and training programs, infrastructure completeness, organizational support on employee performance through satisfaction as a mediating variable. The research method used in this study is a quantitative method. Quantitative research methods are designed to test existing hypotheses. Respondents in this study were 100 training participants. The data analysis used a structural approach to the Equation Model (SEM) assisted by the smart PLS application. There is a significant positive effect between the Education and Training Program variables on employee performance. There is a significant positive effect between the infrastructure completeness variable on employee performance. There is a significant positive effect between organizational support on employee performance. There is a significant positive effect between satisfaction on employee performance. There is a significant positive effect between education and training on satisfaction. There is a significant positive effect between infrastructure completeness on satisfaction. There is significant negative effect between Organizational Support on Satisfaction. There is a significant positive effect between Education and Training Programs on employee performance mediated by satisfaction. there is a significant positive effect between Infrastructure completeness on employee performance mediated by satisfaction. There is a significant negative effect between Organizational Support on employee performance mediated by satisfaction